(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Today banks operate in an extremely globalized, liberalized, privatized and a competitive environment. Indian banking industry has witnessed an incredible growths due to extensive changes that are taking place in the information technology. The development and the increasing progress that is being experienced in the Information and Communication Technology have brought lot of changes in almost all facets of life. In the Banking Industry, it has been in the form of online or e-banking, which is now replacing the traditional banking practice. The e-banking constitutes an electronic alternative network of payments and benefit of services. E-banking has the potential to transform the banking business as it significantly lowers transaction and delivery costs. Today e-banking has experienced phenomenal growth and has become one of the main avenues for banks to deliver their products and services. Online banking has a lot of benefits which add value to customers’ satisfaction in terms of better quality of service offerings and at the same time enable banks gain more competitive advantage over other competitors. There are some associated challenges identified in the study that seem to hinder the success of e-banking services and thus constitute major concern to both financial institutions and customers. This paper aims to present the E-Banking situation and challenges in India.